2022
DOI: 10.1111/ele.13998
|View full text |Cite
|
Sign up to set email alerts
|

Nest architecture is linked with ecological success in songbirds

Abstract: Nests are essential constructions that determine fitness, yet their structure can vary substantially across bird species. While there is evidence supporting a link between nest architecture and the habitat a species occupies, we still ignore what ecological and evolutionary processes are linked to different nest types. Using information on 3175 species of songbirds, we show that-after controlling for latitude and body size-species that build domed nests (i.e. nests with a roof) have smaller ranges, are less li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 62 publications
(90 reference statements)
0
33
0
Order By: Relevance
“…plastic, aluminium foil and plastic string). (Photos: [1,2,4]—Z.J., [3]—Weronika Baranowska). ( b ) The geographical location of studies identified by our literature search that have quantified the presence of ANMs in birds’ nests.…”
Section: Introductionmentioning
confidence: 99%
“…plastic, aluminium foil and plastic string). (Photos: [1,2,4]—Z.J., [3]—Weronika Baranowska). ( b ) The geographical location of studies identified by our literature search that have quantified the presence of ANMs in birds’ nests.…”
Section: Introductionmentioning
confidence: 99%
“…Passeriformes ( passerines, or 'perching birds') is the largest order of birds, comprising approximately 60% of extant avian species and occupying a wide range of ecological niches worldwide. This clade's ecological and evolutionary success has been attributed to many potential factors [1][2][3], including innovation in nest-building behaviours [4][5][6][7][8][9][10]. A well-built nest represents a key component of successful reproduction in many avian species, protecting eggs and chicks from predation and environmental pressures [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nests are built by a range of vertebrate and invertebrate taxa-including fishes, reptiles, amphibians, birds, mammals and insects-to house vulnerable eggs and offspring [1,2]. Nest structures typically hold the eggs of oviparous species and the offspring of both oviparous and viviparous species and, therefore, play a key role in achieving reproductive success [1,[3][4][5]. For example, Medina et al [5] showed that interspecific variation in the design of birds' nests is an important determinant of the evolutionary persistence, and thus success, of species.…”
Section: Introductionmentioning
confidence: 99%
“…Nest structures typically hold the eggs of oviparous species and the offspring of both oviparous and viviparous species and, therefore, play a key role in achieving reproductive success [1,[3][4][5]. For example, Medina et al [5] showed that interspecific variation in the design of birds' nests is an important determinant of the evolutionary persistence, and thus success, of species. Nevertheless, our understanding of the evolutionary ecology of nests and nest building has lagged behind our understanding of the later stages of reproduction, such as incubation behaviours and offspring provisioning, despite the fact that nestsincluding the large burrows of mammals and the enormous structures that house colonies of eusocial insects-have long held a fascination for scientists [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation